2008
DOI: 10.1021/ac702196z
|View full text |Cite
|
Sign up to set email alerts
|

When Machine Tastes Coffee:  Instrumental Approach To Predict the Sensory Profile of Espresso Coffee

Abstract: A robust and reproducible model was developed to predict the sensory profile of espresso coffee from instrumental headspace data. The model is derived from 11 different espresso coffees and validated using 8 additional espressos. The input of the model consists of (i) sensory profiles from a trained panel and (ii) on-line protontransfer reaction mass spectrometry (PTR-MS) data. The experimental PTR-MS conditions were designed to simulate those for the sensory evaluation. Sixteen characteristic ion traces in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 17 publications
1
60
0
1
Order By: Relevance
“…Atmospheric pressure chemical ionization mass spectrometry (APCI-MS) [8][9][10][11][12] and proton transfer reaction mass spectrometry (PTR-MS) [13][14][15][16][17][18][19][20], both equipped with a quadrupole mass filter, have been successfully applied to the online and fast analysis of complex VOC mixtures.…”
Section: Coffee Roastingmentioning
confidence: 99%
“…Atmospheric pressure chemical ionization mass spectrometry (APCI-MS) [8][9][10][11][12] and proton transfer reaction mass spectrometry (PTR-MS) [13][14][15][16][17][18][19][20], both equipped with a quadrupole mass filter, have been successfully applied to the online and fast analysis of complex VOC mixtures.…”
Section: Coffee Roastingmentioning
confidence: 99%
“…Previous studies have shown that delivery of volatile compounds from a matrix to the headspace on hydration is strongly dependent on the physicochemical properties (e.g., hydrophobicity, volatility, molecular size) of the molecule of interest [40,41]. Studies on coffee have shown a tentative identification of compounds by m/z with acetaldehyde, 2,3 butanedione, pyridine, methylacetate and pyrrole predicted to be assigned to m/z of 45, 87, 80, 75 and 68, respectively [42,43]. When evaluating across the calibration curves (n = 3), 68, 75 and 80 were shown to be released to the headspace quickly and 87 and 45 were shown to be released more slowly.…”
Section: Resultsmentioning
confidence: 99%
“…When evaluating across the calibration curves (n = 3), 68, 75 and 80 were shown to be released to the headspace quickly and 87 and 45 were shown to be released more slowly. Assuming that the mass to charge ratio markers indicated by Lindinger et al [42,43] are correct, this would indicate that pyrrol, methylacetate and pyridine could be classified as ''rapid releasers'' and 2,3 butanedione and acetaldehyde as ''slow releasers.'' The TMAX ± SD for the model coffee sample is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The techniques are highly relevant to industry, but for obvious reasons of confidentiality, publications from flavour and food companies are relatively rare. However, the contribution of direct mass spectrometry to research at Nestle was reviewed at the 2007 PTR-MS meeting (Lindinger et al, 2007) and the Nestle team has published some other general reviews of mass spectrometry within the company (Fay et al, 2001;Lindinger et al, 2008). Although direct mass spectrometry was originally developed to measure aroma release during eating, it has found several other uses since it became readily available in the late 1990s, and some applications are described in the following sections.…”
Section: Applicationsmentioning
confidence: 99%
“…A reasonable fit was achieved if an improved version of the Overbosch adaptation effect was included in the Steven's law relationship. A recent example of the second approach involves predicting the sensory quality of coffee from headspace analysis of brewed espresso samples (Lindinger et al, 2008). Here, the mean maximum release intensity was correlated with sensory attributes of coffee using a multivariate statistical approach.…”
Section: Breath-by-breath Analysismentioning
confidence: 99%